Desarrollo de una técnica de PCR Development of a PCR technique for the detection of Fowl adenovirus 4 (FADV-4) in tissue samples - Chávez-Montenegro, Víctor (2021)
It is important to have a PCR technique capable of detecting avian adenovirus 4 with high sensitivity and precision in cell cultures and samples of avian origin. In the present work, a PCR technique was standardized. First, the Internal Reference Material (IRM) was prepared, using cell culture in EB66 cells, infected with FAdV-4; then the virus was purified, the DNA was extracted and the amplicon was quantified. Finally, the temperature gradient test, primer concentration test, sensitivity test and specificity test were carried out using the Q5® High-Fidelity 2X Master PCR kit. Of the five primers used, the HHS*-3 and HHS*-4 primers passed all the tests, with HHS*-3 being the most sensitive as it detected up to 1 pg/µl.